IllustrisTNG in the HSC-SSP: image data release and the major role of mini mergers as drivers of asymmetry and star formation - Bottrell, Connor; Yesuf, Hassen M; Popping, Gergö; Omori, Kiyoaki Christopher; Tang, Shenli; Ding, Xuheng; Pillepich, Annalisa; Nelson, Dylan; Eisert, Lukas; Gao, Hua; Goulding, Andy D; Kalita, Boris S; et al. (Monthly notices of the Royal Astronomical Society, 2024)
At fixed galaxy stellar mass, there is a clear observational connection between structural asymmetry and offset from the star-forming main sequence, ΔSFMS. Herein, we use the TNG50 simulation to investigate the relative roles of major mergers (stellar mass ratios μ ≥ 0.25), minor (0.1 ≤ μ < 0.25), and mini mergers (0.01 ≤ μ < 0.1) in driving this connection amongst star-forming galaxies (SFGs). We use dust radiative transfer post-processing with SKIRT to make a large, public collection of synthetic Hyper Suprime-Cam Subaru Strategic Program (HSC-SSP) images of simulated IllustrisTNG (TNG) galaxies over 0.1 ≤ z ≤ 0.7 with log (M⋆/M⊙) ≥ 9 (∼750 k images). Using their instantaneous star formation rates (SFRs), known merger histories/forecasts, and HSC-SSP asymmetries, we show (1) that TNG50 SFGs qualitatively reproduce the observed trend between ΔSFMS and asymmetry and (2) a strikingly similar trend emerges between ΔSFMS and the time-to-coalescence for mini mergers. Controlling for redshift, stellar mass, environment, and gas fraction, we show that individual mini merger events yield small enhancements in SFRs and asymmetries that are sustained on long time-scales (at least ∼3 Gyr after coalescence, on average) - in contrast to major/minor merger remnants which peak at much greater amplitudes but are consistent with controls only ∼1 Gyr after coalescence. Integrating the boosts in SFRs and asymmetries driven by μ ≥ 0.01 mergers since z = 0.7 in TNG50 SFGs, we show that mini mergers are responsible for (i) 55 per cent of all merger-driven star formation and (ii) 70 per cent of merger-driven asymmetric structure. Due to their relative frequency and prolonged boost time-scales, mini mergers dominate over their minor and major counterparts in driving star formation and asymmetry in SFGs.